Healthcare at crossroads: cancer in Pakistan - prevalence and challenges - Ali, Dua; Ahmed Waqas, Saad (Journal of the Pakistan Medical Association, 2025)
Dear Editor, Cancer stands as a formidable global threat, claiming millions of lives each year. The Globocan 2018 presented an estimation of 18.1 million new cases of cancer and 9.6 million deaths, which was a significant increase from 20121. The impact of this disease is adverse in Low-Middle-Income countries. A study conducted by Jonathan M. Kocarnik et al estimates cancer burden and trends globally for 204 countries by Sociodemographic Index (SDI) quintiles. The results showed the largest percentage increases in cancer incidence and mortality during the last decade occurred in the lower SDI quintiles.2 A thorough online literature search was carried out on Pubmed, and Pakimedinet which showed not much significant action being done for prevention of the disease. Even though the trend is alarming as seen in data from Shaukat Khanum Memorial Cancer Hospital and Research Centre highlighting the prevalence of breast cancer among Pakistani females, with one in nine women facing a lifetime risk.3 Various factors contribute to the prevalence of cancer, including frequent usage of gutka and paan coupled with smoking, which has placed Pakistan as the second-largest consumer of smokeless tobacco4. Notably, the deficiency of vitamin D, and high prevalence of Hepatitis B and C play pivotal roles contributing to a high percentage of breast and liver cancers per year, respectively. The evident contrast in trend between countries of high and low Sociodemographic Index (SDI) quintiles is attributed to inadequate control of risk factors such as lack of early presentation and low cancer awareness. A few context-specific barriers like lack of family support and religious beliefs create hindrances in cancer prevention. In certain cases, women are denied the opportunity to undergo screening process by their husbands primarily driven by fear of humiliation. Implementing these findings in the country could help mitigate the cancer crisis. Some of the ways this could be applied is by; introducing policies and campaigns that restrict intake and smoking of tobacco products, promoting uptake of HPV vaccines, integrating healthy dietary practices into daily lives, prolonged breastfeeding and providing awareness about self-examination (especially in breast cancer). Further, affordable screening equipment, a well-trained workforce, and minimizing loss to follow-up between screening, diagnosis, and treatment must be introduced, especially in rural areas. Curtailing this escalating crisis demands commitment at both the individual and government levels by ensuring awareness and affordable treatment that is effective in combating the impact of cancer on the population.